Allen Buchanan, Our Moral Fate (2020) - Calderini, Guido (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2023)
In debates surrounding the biomedical enhancement of human morality, it is widely believed that morality was evolutionarily shaped to be rigidly tribal. Allen Buchanan challenges this assumption by making the case that a plastic morality that responds to our environment would be evolutionarily favored, and thus the best way to shape human morality going forward would not be through biomedical interventions, but by designing better institutions.